2005
DOI: 10.1038/sj.onc.1209135
|View full text |Cite
|
Sign up to set email alerts
|

TRF2 inhibition promotes anchorage-independent growth of telomerase-positive human fibroblasts

Abstract: Although telomere instability is observed in human tumors and is associated with the development of cancers in mice, it has yet to be established that it can contribute to the malignant transformation of human cells. We show here that in checkpoint-compromised telomerase-positive human fibroblasts an episode of TRF2 inhibition promotes heritable changes that increase the ability to grow in soft agar, but not tumor growth in nude mice. This transforming activity is associated to a burst of telomere instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
(51 reference statements)
2
14
0
Order By: Relevance
“…Accordingly, TRF2-depleted telomeres appear deprotected or uncapped and can undergo end-to-end fusions and subsequent chromosome abnormalities (4,18,19). Along the same line, we recently showed that, in checkpoint-compromised telomerasepositive human fibroblasts, TRF2 inhibition promotes heritable changes, associated with a burst of telomere instability, that increase the ability to grow in soft agar (20). Strikingly, we also reported that the expression of a dominant-negative form of TRF2 in a melanoma cell line markedly inhibits its tumorigenic ability (21), suggesting that TRF2 inhibition can also counteract some of the steps involved in tumorigenesis.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Accordingly, TRF2-depleted telomeres appear deprotected or uncapped and can undergo end-to-end fusions and subsequent chromosome abnormalities (4,18,19). Along the same line, we recently showed that, in checkpoint-compromised telomerasepositive human fibroblasts, TRF2 inhibition promotes heritable changes, associated with a burst of telomere instability, that increase the ability to grow in soft agar (20). Strikingly, we also reported that the expression of a dominant-negative form of TRF2 in a melanoma cell line markedly inhibits its tumorigenic ability (21), suggesting that TRF2 inhibition can also counteract some of the steps involved in tumorigenesis.…”
Section: Introductionmentioning
confidence: 63%
“…Transformed BJ fibroblasts expressing hTERT and SV40 early region (BJ-EHLT) were maintained as previously described (20). Human M14 melanoma, CG5 breast carcinoma, and HT29 colon carcinoma lines were previously described (45)(46)(47).…”
Section: Methodsmentioning
confidence: 99%
“…TRF2 inhibition has been shown to promote mutations that increase the ability of immortalised cells to grow in soft agar, although the capacity of tumour growth in nude mice was not similarly increased (Brunori et al, 2006). This transforming activity was associated with a burst of telomere instability, independent of telomere length reduction.…”
Section: Is Telomere Shortening Too Fast or Telomerase Too Slow?mentioning
confidence: 85%
“…Human immortilized BJ-hTERT and transformed BJ-EHLT/RasV12 fibroblasts were obtained and maintained as described (57,58). The wild-type and p53-deficient colon carcinoma HCT116 cells were obtained by Dr Vogelstein, Johns Hopkins University.…”
Section: Methodsmentioning
confidence: 99%